Emerging Strategies and Integrated Systems Microbiology Technologies for Biodiscovery of Marine Bioactive Compounds - Rocha-Martin, J.; Harrington, C.; Dobson, A.; O'Gara, Fergal (M D P I AG, 2014)
Marine microorganisms continue to be a source of structurally and biologically novel compounds with potential use in the biotechnology industry. The unique physiochemical properties of the marine environment (such as pH, pressure, temperature, osmolarity) and uncommon functional groups (such as isonitrile, dichloroimine, isocyanate, and halogenated functional groups) are frequently found in marine metabolites. These facts have resulted in the production of bioactive substances with different properties than those found in terrestrial habitats. In fact, the marine environment contains a relatively untapped reservoir of bioactivity. Recent advances in genomics, metagenomics, proteomics, combinatorial biosynthesis, synthetic biology, screening methods, expression systems, bioinformatics, and the ever increasing availability of sequenced genomes provides us with more opportunities than ever in the discovery of novel bioactive compounds and biocatalysts. The combination of these advanced techniques with traditional techniques, together with the use of dereplication strategies to eliminate known compounds, provides a powerful tool in the discovery of novel marine bioactive compounds. This review outlines and discusses the emerging strategies for the biodiscovery of these bioactive compounds.